Invisibility and selectivity. Introduction to the special issue on Dutch overseas migration in the nineteenth and twentieth century - Schrover, Marlou; van Faassen, Marijke (TSEG - The Low Countries Journal of Social and Economic History, 2010)
Invisibility and selectivity. Introduction to the special issue on Dutch overseas emigration in the nineteenth and twentieth century. The contributors to this special issue describe the emigration of people from the Netherlands to the most important overseas destinations (the usa, Canada and Australia) in the nineteenth and the twentieth century. Part of the Dutch (overseas) emigrants formed strongly separated communities. Dutch emigrants were also rather invisible. In North America we see a combination of separateness and invisibility, in Australia mainly invisibility. Both in the nineteenth and in the twentieth century, migration was highly selective (with differences according to religion, class, ethnicity and gender). Only in the twentieth century (and especially after 1945) there was a strong influence of government policy on migration. In this issue, the comparison of emigration from one country – the Netherlands – to several destinations and the comparison over time show the influences of the societal context of the country of origin on the formation of Dutch emigrant communities.